The two-probe device for automatic measurement of the reflection coefficient - Ільницький, Л.Я.; Іванов, В.О.; Богатир, В.Т. (Proceedings of National Aviation University (archive), 2004)
The two-probe device for automatic measurement of the reflection coefficient in the HF range is proposed and analyzed. The main parts in the instrument control system are the sum-and-difference bridge and the microprocessor.